The Effects of Gamma-Ray on the Mechanical Properties of Zr-Based Bulk Metallic Glass - L. H., Shah (Universiti Malaysia Pahang, 2012)
The effect of gamma-ray irradiation on the mechanical properties of Zr55Ni5Al10Cu30 bulk metallic glass (BMG) was investigated. The samples were irradiated with a gamma-ray dose up to 2090.24 kGy prior to mechanical property investigations. Vickers hardness test, nano-indentation test as well as speed of sound measurements in order to calculate the material’s elastic moduli were conducted. An x-ray diffractogram device was also utilized to observe the BMG’s devitrification behavior. Results confirm that no significant changes were observed for any of the samples. XRD spectra of irradiated BMGs also show uniform broad peaks, indicating an amorphous structure inside the sample. This result indicates that a gamma-ray irradiation dose of up to2090.24 kGy does not change the mechanical properties and the microstructure of the material, thus making it a good future structural candidate for gamma-ray rich environments.